Common procedures of remote measurement-based care in an integrated behavioural health context: protocol for a scoping review. Issue 9 (28th September 2022) - Richardson, Eric; Hogan, Timothy P; Shimada, Stephanie L; Sliwinski, Samantha K; Kim, Bo
Abstract : Introduction: Integrated behavioural health, a model of care that embeds mental health services in primary care, can potentially increase access to mental healthcare. With the increase in health information technologies, remote measurement-based care (RMBC) presents an opportunity to improve support of integrated care. This scoping review will comprehensively examine what common procedures are followed when RMBC for mental health is tested in integrated care settings. Methods and analysis: Based on an established six-step framework for conducting scoping reviews, we will search PubMed, Embase, PsycINFO, Cochrane, EBSCOhost and Web of Science with search terms related to 'integrated care' and 'RMBC'. Articles published from 2015 onwards, in English, including an intervention that meets our definition of RMBC, and are conducted in collaboration with primary care or in a primary care setting will be included. After data extraction, we will categorise key findings along the following dimensions: (1) common delivery practices of RMBC; (2) common technologies and instruments used and (3) most common barriers and facilitators when implementing RMBC in an integrated care model. Ethics and dissemination: Ethics approval is not required for this scoping review. For maximum impact, we will disseminate the findings to the scientific community (via publication in a peer-reviewed journal and at national conferences) and to the broader healthcare community. We will share findings with the broader healthcare community through our research centre's existing stakeholder communication structures and through guidance from our multidisciplinary research team. These key stakeholder relationships will continue to guide our subsequent RMBC research following the review.